Agronomic performance of transgenic soybean cultivars in Brazilian Cerrado (Acta Scientiarum. Agronomy, 2019)
The productive capacity of soybeans is associated with the adaptation of the culture to the cultivation environment. Factors such as a high number of pods, the weight of a thousand grains, and grain number are essential factors in determining cultivars of high productive potential. The launching of new varieties associated with new technologies makes it necessary to know the performance of these varieties in different growing environments. This study aimed to analyze the agronomic performance of transgenic soybean cultivars under Cerrado conditions. The experimental design used completely randomized blocks; six of the twelve cultivars used RR1 technology and the remaining six used RR2BT. The cultivars were grown in five distinct locations in the southwest region of Goiás. The results demonstrated no increments in the grain yield of the RR1 or RR2BT technologies and the precocity of the cultivars also did not favor an increase in grain yield. The localities of Jataí and Rio Verde did not influence the cultivar cycle.